Effect of chemicals and GA3 on the distribution of endogenous hormones and carbohydrate and germination during the grapevine plant dormancy - WU Yue-yan (浙江大学学报. 农业与生命科学版, 2004)
Treatment in which 15% or 20% lime nitrogen was smeared onto buds of grapevine when their deep dormancy was over significantly decreased ABA content of buds at the middle and lower portion of the shoots but increased GA and IAA content. Treatment with 18% NH4NO3 slightly increased IAA and GA content of the lower buds, whereas remarkably decreased ABA content. The degradation of starch in the middle and lower buds was enhanced by the above treatments, thus resulting in relatively high concentration of soluble sugar in these buds. The accumulation of soluble sugar was thought to be beneficial to germination of buds so that bud-break occurred 7 days earlier than that of control. Treating of the vines with 100 and 150 mg/L GA3 were effective for significant decrease in ABA content but substantially increased GA and IAA content. It was noted that the amount of endogenous hormones in the middle to upper par buds changed more obviously than in the lower part buds. The relatively low starch content and high soluble sugar content of the supper and middle part buds as compared to the lower part buds were considered to the cause of uneven bud bursting along the shoots.